Kinetic study of microwave-assisted alkaline hydrolysis of Jatropha curcas oil - Yusuf, N.R. (American Institute of Physics Inc., 2016)
The kinetics of hydrolysis of Jatropha curcas oil under microwave irradation in the presence of alkaline solution was studied. The temperature of 50°C, 65°C and 80°C were studied in the range of optimum condition of 1.75 M catalyst, solvent/oil ratio of (1: 68) and 15 minutes reaction time. The rate constants of oil hydrolysis are corresponding to triglyceride disappearance concentration. The rates of reaction for fatty acids production was determined by pseudo first order. The activation energy (Ea) achieved at 30.61 kJ/mol is lower using conventional method. This conclude that the rate of reaction via microwave heating is less temperature sensitive therefore reaction can be obtained at lower temperature. © 2016 Author(s).